2020
DOI: 10.7759/cureus.6943
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Scoring Systems in Predicting the Severity of Acute Pancreatitis: A Prospective Observational Study

Abstract: Background Acute pancreatitis (AP) is an inflammatory condition of the pancreas mostly due to alcohol or gallstones. Various scoring systems were involved in identifying the severity of the disease. The standard single score to identifying the severity remains uncertain. Methodology This prospective observational study was carried out for two years in a tertiary care center from South India. The diagnosis of AP was made based on Atlanta criteria, and a total of 164 patients were included. All patients were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 14 publications
1
38
0
2
Order By: Relevance
“…These changes can increase the specificity while slightly reducing the sensitivity of the four scoring systems. CTSI and MTSI are good predictors of both mortality and AP severity [27,40]. Although their calculation require radiological expertise, they provide more precise information if they are combined with the four aforementioned scoring systems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These changes can increase the specificity while slightly reducing the sensitivity of the four scoring systems. CTSI and MTSI are good predictors of both mortality and AP severity [27,40]. Although their calculation require radiological expertise, they provide more precise information if they are combined with the four aforementioned scoring systems in the future.…”
Section: Discussionmentioning
confidence: 99%
“…APACHE and BISAP scores were not calculated in any of these studies, nor was AWS a complication reported in either study. In a study by Venkatesh et al, a comparison of scoring systems in 164 patients (115 with AAP) was studied, but without the component of alcohol withdrawal [ 16 ]. Only 23% (40/168) of patients in a study from Delhi was due to AAP [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Ranson's score diagnostic accuracy on admission is higher for prediction of severity, organ failure, and mortality based on receiver operator characteristic curves. 25,26 These scoring systems may be used for predicting the severity and mortality of acute pancreatitis in patients with COVID-19.…”
Section: Coronavirus Disease 2019 and Pathogenic Mechanismsmentioning
confidence: 99%